Antibody responses against influenza A decline with successive years of annual influenza vaccination - Sheena G. Sullivan; Arseniy Khvorov; Louise Carolan; Leslie Dowson; A. Jessica Hadiprodjo; Stephany Sánchez-Ovando; Yi Liu; Vivian K. Y. Leung; David Hodgson; Christopher C. Blyth; Marion Macnish; Allen C. Cheng; et al. (npj Vaccines)
Abstract Influenza vaccine effectiveness and immunogenicity can be compromised with repeated vaccination. We assessed immunological markers in a cohort of healthcare workers (HCW) from six public hospitals around Australia during 2020–2021. Sera were collected pre-vaccination and ~14 and ~180 days post-vaccination and assessed in haemagglutination inhibition assay against egg-grown vaccine and equivalent cell-grown viruses. Responses to vaccination were compared by the number of prior vaccinations. Baseline sera were available for 595 HCW in 2020 and 1031 in 2021. 5% had not been vaccinated during five years prior to enrolment and 55% had been vaccinated every year. Post-vaccination titres for all vaccine antigens were lowest among HCW vaccinated in all 5-prior years and highest among HCW with 0 or 1 prior vaccinations, even after adjustment. This was observed for both influenza A subtypes and was dependent on pre-vaccination titre. Expanded cohorts are needed to better understand how this translates to vaccine effectiveness.